Learning Algebraic Formula | The Formula of (a-b)²
The algebra formula, (a-b)², is used to calculate the square of a binomial. It is also called the formula used to calculate the square of the difference of 2 identities or terms. We have covered the formula and a solved example for your better understanding of the formula of (a-b)². So, let’s dive in:
Algebra Formula: (a-b)² Proof
Now, the formula is:
(a-b)²=a²-2ab+b²
But if you are not sure about it, here is how you can prove it:
(a-b)²=(a-b)(a-b)
⇒ a(a-b)-b(a-b)
⇒ a²-ab-ab+b²
⇒ a²-2ab+b²
Related Read: https://mytutorsource.com/blog/how-mts-tutors-can-help-you-in-improving-your-mathematics/
Other Formulae That You Should Know Of
- (a+b)²
𝑎2 + 2𝑎𝑏 + 𝑏2
- Perimeter of Parallelogram
P=2(a+b)
A Solved Example
Find out the value of (2a — 3b)2
Solution
(2a — 3b)2 = (2a)2 + (3b)2–2(2a)(3b)
= 4a2 + 9b2–2(2a)(3b)
= 4a2 + 9b2–12ab
Therefore,
(3a — 2b)2 = 4a2 + 9b2–12ab
And that’s the formula of (a-b)², explained and solved, for you.